Personality Factors, Affect, and Autonomy Support as Predictors of Life Satisfaction - Puente Díaz, Rogelio; Universidad Anahuac Mexico Norte (2012)
This research examined the predictors of subjective well-being. Two studies were conducted. Our first study involved the administration of life satisfaction, personality, affection, need satisfaction, and self-construal questionnaires to 369 college students from Mexico. The results showed that extroversion and neuroticism had a significant direct effect on positive and negative affect, respectively, and indirect effects on life satisfaction. Results also revealed that autonomy support, defined as the ability to perceive oneself as the source of one’s behavior, was a significant and positive predictor of life satisfaction. To address some of the limitations from study I, study II used the World Values Survey to examine the effects of autonomy support on life satisfaction and domain satisfaction among representative samples from Mexico, Argentina, and Brazil. The findings showed that the autonomy support was a significant predictor of life satisfaction and domain satisfaction in all three countries. The implications of the results are discussed.